Probiotics modulate gastrointestinal microbiota after Helicobacter pylori eradication: A multicenter randomized double-blind placebo-controlled trial - He, Cong; Xie, Yong; Zhu, Yin; Zhuang, Kun; Huo, Lijuan; Yu, Yong; Guo, Qiang; Shu, Xu; Xiong, Zhijuan; Zhang, Zhenyu; Lyu, Bin; Lu, Nonghua (Frontiers in Immunology, 2022)
Background: Helicobacter pylori (H. pylori) eradication has been reported to cause short-term disruption of gut microbiota. It is acknowledged that probiotics supplementation mitigates side effects induced by H. pylori eradication, yet its role on alleviating dysbiosis of microbiota is obscure. Objectives: To evaluate the impact of probiotics on gastrointestinal microbiota after eradication therapy. Methods: This was a multicenter, double-blinded, randomized trial done at seven centers in China. A total of 276 treatment-naïve H. pylori-positive patients were randomly assigned to receive 14-day bismuth-containing quadruple therapy (esomeprazole, bismuth, amoxicillin, furazolidone) combined with probiotics (Bifidobacterium Tetragenous viable Bacteria Tablets) (n=140) or placebo (n=136) for 28 days. Saliva, gastric mucosa and fecal samples were collected before and after therapy for 16S rRNA gene sequencing. Results: The incidence of gastrointestinal adverse events was lower in probiotics group compared to placebo group (23.6% vs 37.7%, p=0.016), while there was no significant difference in eradication rate. We found dramatic perturbations of gut microbiota immediately following eradication, with the predominance of Proteobacteria in replacement of commensal Firmicutes and Bacteroidetes, and gradually restored after two weeks. The reduction of gut Bacteroidetes caused by eradication drugs was neutralized with probiotics supplementation. The gastric microbiota was completely reconstituted with H. pylori depleted and other taxa flourished. Of note, patients treated with probiotics showed smaller fluctuations of gastric microbiota compared to those with placebo. We also observed changes of saliva microbiota after H. pylori eradication, illustrated by the overgrowth of Neisseria and depletion of Streptococcus. The expansion of some pathogenic genera, including Porphyromonas, Leptotrichia, in the mouth was suppressed by probiotics. Conclusion: This study not only demonstrated the beneficial effect of probiotics implementation on side events during H. pylori eradication but also provided a comprehensive profile of microbiome alterations along gastrointestinal tract that modulated by probiotics.